Editors Speak Out on Refereeing ; Another kind of Evaluation ; Writing for Professional Publications: Ways to Increase your success. - Kathleen Warren; Jim Shaner (Journal of Applied Communications, 1985)
Reviews of "Editors Speak Out on Refereeing," by Bruce M. Smith and Pauline B. Gough; "Another Kind of Evaluation," by M.F. Smith and Yvonna S. Lincoln; "Writing for Professional Publications: Ways to Increase your Success," by Kenneth T. Henson.